An Overview of The Learning Motivation Of Early Adolescent Student Raised by Single Parent - A. Alifiya Tenriesa; Eva Meizara Puspita Dewi; Novita Maulidya Djalal (PT ARRUS Intelektual Indonesia, 2023)
This study aims to describe the learning motivation of early adolescent female student raised by single father. Respondent in this study were early adolescent individual who were raised by one parent, namely a single father because of the death of the mother. The significant other in this study is the father of the respondent. This study uses a qualitative method with a case study approach with data collection techniques, namely interviews and documentation. The results of data analysis in this study indicate that respondent have optimal learning motivation. Respondents set goals, maintain commitment and initiative in learning. The optimal respondent's learning motivation is influenced by the father's involvement in education as a guide, motivator, and facilitator. Respondents also received social support from grandmother and friends who helped respondents during the learning process. This research is expected to provide knowledge to single fathers regarding involvement in children's learning processes, especially in their early teens.